Biofabrication Of Gold Nanoparticles Using Leaf Extract Of Ficus Benghalensis And Their Characterization - R. M. TRIPATHI,; ARCHANA SHRIVASTAV,; B. R. SHRIVASTAV, (International Journal of Pharma and Bio Sciences, 2012)
We report here the biofabrication of gold nanoparticles (AuNPs) using leaf extract of Ficus benghalensis (a national tree of India). This method is rapid, cost effective, non toxic and eco-friendly and these features are making it more attractive for biomedical application. Aqueous solution of F. benghalensis leaf extract was used as reducing and capping agent in the synthesis of AuNPs. UV–Vis spectroscopy was used to monitor the quantitative formation of AuNPs. UV-Vis spectrum of the reaction solution showed a peak at 527 nm corresponding to the surface Plasmon resonance of gold nanoparticles. Particle size distribution was analysed by Dynamic light scattering (DLS). Further investigation was carried out by Fourier Transform Infrared Spectroscopy (FTIR), provides confirmation for the presence of proteins as capping agent, which support in enhancing the stability of AuNPs. The morphology and particle size was confirmed by Transmission Electron microscopy (TEM) which showed formation of well-dispersed AuNPs in the range of 17-50 nm with spherical in shape.